BARRIERS TO INNOVATION AND THE CONTRIBUTION FROM THE INSTITUTIONAL PERSPECTIVE: A MULTIPLE CASE STUDY (INMR - Innovation & Management Review, 2008)
The cadence imposed on the organizations by the context in which they are inserted, as well as the competitive structure in which they dispute their markets, oblige them to look for ways to innovate and to differentiate from their competitors, in order to maintain solid and competitive. On the other hand, there are several factors that contribute to the organizations to become more homogenous. In this context, this study aims to observe, analyse and discuss the materialization of barriers to the adoption of innovations and the main opportunities underlying the road transport of passengers sector, considering the interpretation of three strategic actors of companies from this sector in the state of Paraná. A theoretical referential is analysed and adopted. The methodology consista in a descriptive and exploratory case study. The conclusion is that the way in which each organization, taking its leaders considerations, interpret the same identified barriers differs significantly in certain aspect, as well as these barriers are differently understood as opportunities inside this economic sector, a fact that can be, to some extent, attributed to the differences in the interpretive schemes and the referential context of each case.